2016
DOI: 10.5301/jabfm.5000262
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the Elastic Properties of ex vivo Porcine Corneas Subjected to Inflation Test after Cross-Linking Treatment

Abstract: The inflation test has been proven to be a valuable tool for the investigation of corneal biomechanics, maintaining both integrity and geometry of corneal tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 39 publications
0
23
1
Order By: Relevance
“…The biomechanical properties of the cornea are associated with the development of corneal diseases such as keratoconus, ectasia after refractive surgery, and possible glaucoma progression [ 1 4 ]. Hence, there has been a recent surge of interest in assessing corneal biomechanical properties due to potential clinical implications [ 5 7 ]. Moreover, the biomechanical properties of the cornea have been proposed to directly affect intraocular pressure (IOP) measurements, especially for normal tension glaucoma [ 8 , 9 ], and are becoming recognized as necessary for the calibration of IOP in different moduli of tonometers [ 10 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The biomechanical properties of the cornea are associated with the development of corneal diseases such as keratoconus, ectasia after refractive surgery, and possible glaucoma progression [ 1 4 ]. Hence, there has been a recent surge of interest in assessing corneal biomechanical properties due to potential clinical implications [ 5 7 ]. Moreover, the biomechanical properties of the cornea have been proposed to directly affect intraocular pressure (IOP) measurements, especially for normal tension glaucoma [ 8 , 9 ], and are becoming recognized as necessary for the calibration of IOP in different moduli of tonometers [ 10 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The J-shaped stress-strain curve obtained here for the corneal tissue is commonly observed in animal and human corneas stressed through both the tensile and inflation tests (2-3-4-5-6-7-8-9-10-11-12-13-14-15-16). Similarly to other soft and dense biological tissues, cornea can be considered a composite material consisting of a proteoglycan-based matrix reinforced by collagen fibers (36, 37).…”
Section: Discussionmentioning
confidence: 57%
“…The tensile test represents a very popular method to assess the biomechanical properties of cornea. Specifically, rabbit (3-4-5-6-7), bovine (3, 8) and porcine (9-10-11) models have been frequently analyzed. Often, the biomechanical properties of the animal corneal tissue have been compared with those of the human cornea (3, 7, 8).…”
Section: Introductionmentioning
confidence: 99%
“…Zhang and colleagues studied the corneal biomechanical properties after CXL with a uniaxial tensile test [19], and they found that corneal elastic moduli significantly increased after CXL. Matteoli et al measured porcine corneal biomechanical properties with corneal inflation experiments [18] and found that corneal elastic modulus increased after CXL under high IOP, while no significant difference was found within the physiological range of IOP (15-30mmHg).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies that used in vitro experiments have reported the variations of corneal biomechanical properties after CXL [16][17][18][19], showing that corneal stiffness increased after CXL. Some researchers have reported the variation of corneal biomechanical parameters provided by Corvis, Steinberg et al find that the first applanation time (A1T) increased and the second applanation time (A2T) decreased 3 months after CXL [20].…”
Section: Introductionmentioning
confidence: 99%